Dermatological Manifestations in Dengue Fever - Mariam Sheikh, Sidrah Riaz, Ikram ur Rahim, Alia Waheed, Abdullah Farooq Khan, Nadia Saif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of skin & mucosal manifestations in dengue fever patients. Study design: Cross-sectional study. Place and duration of study: Patients admitted in dermatology & medicine departments of Akhtar Saeed Trust Hospital Lahore were included in the study. Method of study: This cross-sectional study was conducted in departments of dermatology & medicine at Akhtar Saeed Trust Hospital Lahore for a period of 3 months from Separation 3021 till December 2021. After taking consent a total of 60 patients of suspected dengue fever were enrolled for this study. Their demographic data was noted down with skin & mucosal findings in a predesigned performa. Their frequencies were calculated & analysed in SPSS version 11. Results: Out of 60 patients, 38 patients (63.3%) were males & 22 patients (36.6%) were females. Mean age of patients was 35.20 years. 13 patients (21.6%) had no skin findings and 47 patients (78.4%) had skin findings. The commonest skin finding was pruritus present in 24 patients (40%), followed by facial flushing in 15 patients (25%). Petechial rash and burning sensation were found in 7 patients (11.6%). Among the mucosal findings, eye involvement was the commonest present in 15 patients (25%). Conclusion: Cutaneous and mucosal manifestations are an important part of dengue fever. These findings also help in assessing the disease progress.